Envisioning the Future of Special Education Personnel Preparation in a Standards-Based Era. (October 2015) - Leko, Melinda M.; Brownell, Mary T.; Sindelar, Paul T.; Kiely, Mary Theresa
The authors consider the future of special education personnel preparation by responding to an overarching question: What frameworks might teacher educators use as a basis to promote special education teacher effective performance now and in the future? In answering this question, they summarize current trends in the context of schooling and special education (i.e., Common Core State Standards [CCSS], multi-tiered systems of support [MTSS]) and what these contexts demand of special education teachers. The authors propose a practice-based model for fostering effective special education teacher performance. Grounded in the science of learning, the model includes approaches in teacher education that align with this literature. Implications for implementing the model are provided, which recognize current constraints on schools and colleges of education, to better promote this model for fostering effective performance.